Peran Guru Akidah Akhlak Dalam Mengatasi Krisis Moralitas Di MTS Negeri 2 Surakarta - Alhafidz, Sena Aji; Mustofa, Triono Ali (Jayapangus Press, 2025)
This study aims to examine the role of Akidah Akhlak teachers in overcoming the morality crisis at MTsN 2 Surakarta. The phenomenon of moral decline among adolescents, such as lack of respect, bullying, and abuse of technology, is a serious challenge in the world of education, especially in the formation of student character. This research uses a qualitative approach with data collection techniques through direct observation, in-depth interviews with two Akidah Akhlak teachers, as well as supporting documentation such as lesson plans and student behavior records. Data validity is strengthened through source and method triangulation. The results showed that Akidah Akhlak teachers play a strategic role in student character building through value learning in the classroom, involvement in extracurricular activities, and the creation of a school culture that supports morality. Teachers become role models and facilitators of Islamic values in students' lives. Direct learning actively involves students to develop understanding, critical thinking, and integrated skills, while the indirect learning process runs simultaneously as part of educational activities even though it is not specifically designed. In conclusion, character education based on Islamic values has proven effective in responding to the moral crisis in schools. Its success is determined by the active role of teachers, the involvement of parents, and the consistency of school policies. This research confirms that character building is a social practice that requires collaboration across parties and approaches according to the context of the times, opening up opportunities for the development of models that are more responsive to the needs of today's youth.